Religious brothers as Superiors in clerical religious institutes of pontifical law and in clerical societies of apostolic life of pontifical law - Stokłosa, Marek (Prawo Kanoniczne, 2023)
Pope Francis's rescript, published on 18 May 2022, contains four paragraphs regulating the entrustment of the office of superior to members who have not received the sacrament of Holy Orders in clerical institutes of consecrated life and clerical societies of apostolic life of pontifical law, by way of derogation from can. 588 §2 CIC/83 and from the norms of proper law that refer to that canon. According to the content of the canon, the offices of superior in such entities could be entrusted only to members who are clerics. In exceptional cases, the then Congregation for Institutes of Consecrated Life and Societies of Apostolic Life granted dispensations from can. 588 §2 CIC/83, permitting the appointment of an unordained member as a local superior. The new regulations introduced by the papal rescript apply exclusively to clerical institutes of consecrated life and clerical societies of apostolic life of pontifical law. They do not, however, extend to clerical institutes and clerical societies of diocesan right. In the case of these institutes, it remains possible for the competent diocesan bishop to submit a request to the Dicastery for Institutes of Consecrated Life and Societies of Apostolic Life to entrust the office of local superior to a member of the institute or society who does not belong to the clerical state. In accordance with the rescript, a member of a clerical institute or society of pontifical law who has not received the sacrament of Holy Orders may be appointed local superior by the supreme superior with the consent of his council (§1). In this situation, the rescript no longer provides for any intervention by the Holy See. The rescript also allows for the appointment of such a member as a major superior, provided that written authorization is obtained from the Dicastery for Institutes of Consecrated Life and Societies of Apostolic Life. This authorization is granted at the request of the supreme superior, after obtaining the consent of his council (§2). The entrustment of the office of major superior may also take place through election. However, the confirmation of the election of a member who is not a presbyter must be carried out by the Dicastery for Institutes of Consecrated Life and Societies of Apostolic Life (§3). Pope Francis's rescript also allows for the election of a member who is not a cleric as the supreme superior of a clerical institute of consecrated life or a clerical society of apostolic life of pontifical law. This election is carried out by the general chapter, in accordance with the constitutions of the institute or socjety. However it requires the approval by the Dicastery for Institutes of Consecrated Life and Societies of Apostolic Life.